Comedians' Trait Level and Stage Personalities: Evidence for Goal-Directed Personality Adaptation. (April 2020) - Irwing, Paul; Cook, Clare; Pollet, Thomas V.; Hughes, David J.
Recent findings have shown that both trait levels of personality and situational variability in its expression are of importance. So here, the Big Five personality traits of 77 professional and 125 amateur stand-up comedians were compared with two large matched samples ( N > 100, 000). The comedians were also observed while performing, which enabled a comparison of their stage personalities with situational requirements on 10 selected NEO-PIR facets. Both amateurs and professionals showed higher openness-to-experience, extraversion, and lower conscientiousness than their norm samples, while professionals also evidenced greater neuroticism. Irrespective of trait standing, with regard to most NEO-PIR facets, professionals expressed the appropriate on-stage persona and were better able to regulate their personality to conform to situational requirements than amateurs. This is consistent with research showing that individuals regulate their personality to conform to situational and goal requirements, and adds the finding that successful comedians demonstrate enhanced adaptability compared with amateurs.